Strategi Optimasi Produksi Getah Karet Perumda Perkebunan Kahyangan Jember (International Forum of Researchers and Lecturers, 2024)
Rubber latex is a raw material for Indonesia's strategic plantations and is the largest contributor to the country's foreign exchange after palm oil. Several places in Indonesia have land conditions that are suitable for rubber plantations, one of which is the rubber plantation owned by Perumda Perkebunan Kahyangan Jember. However, in recent years, income from Perumda Perkebunan Kahyangan Jember has continued to decline, so it is necessary to formulate an optimization strategy which is expected to have a positive impact and be able to increase rubber latex production in Perumda Perkebunan Kahyangan Jember. This research uses SWOT and QSPM analysis methods. The results of the research show that there are several factors that influence rubber latex production, both internal and external factors, from these factors several alternative strategies have been produced, including the use of protective umbrellas, producing high quality rubber raw materials, improving production facilities and infrastructure, optimizing technology. for production and promotion. A suitable strategy to be implemented at Perumda Perkebunan Kahyangan Jember is the use of protective umbrellas because the application is quite simple and can function to maintain the quality of production and the quality of rubber latex..